STRATEGI PENGEMBANGAN BISNIS SMKS BUMI SEJAHTERA DI KECAMATAN CIBUNGBULANG KABUPATEN BOGOR MENUJU PENDIDIKAN 4.0 - Marjania Ayu Azizah; Musa Hubeis; Setiadi Johar (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The industrial era is changing rapidly from the 1st industrial revolution until now become the 4th industrial revolution or Industry 4.0 Era. As the supplier of the workforce, vocational schools need to follow the industrial changes trough the education they gave to the pupils. The education system that accommodate the 4th industrial revolution is Education 4.0 system. The purpose of this study is to build development strategies for SMKS Bumi Sejahtera, a vocational senior high school in Bogor Regency, in term of implementing Education 4.0 system. This study was starting with analyzing the school management and environment by applying internal and external evaluation and continued by analyzing the business position. Purposive sampling technique was used by aiming stakeholders and users who understand SMKS Bumi Sejahtera’s management or vocational high school in general. Analyzing processes were included environmental analysis using IFE and EFE matrics, business potition was analyzed by looking into the IE matric. Alternative strategies were analyzed from SWOT matrics and the priorities are based on QSPM. Findings indicate that the school already in a good business position, so an intensive strategy is recommended. Implementation steps are made to help the school in running the alternatives strategies.